A Family of Microporous Materials Formed by Sn(IV) Phosphonate Nanoparticles - Subbiah, Ayyappan; Pyle, David; Rowland, Adam; Huang, Jin; Narayanan, R. Aravinda; Thiyagarajan, P; Zoń, Jerzy; Clearfield, Abraham (Journal of the American Chemical Society, 2005)
Reaction of Sn(IV) with phosphonic acids results in the formation of tin phosphonates with a spherical morphology arising from the aggregation of nanosized individual particles. Under high magnification, the spheres are shown to be porous with surface areas of 200−515 m2/g, depending on the type of phosphonic acid and the synthesis conditions used. The pores are largely micro in nature but also somewhat dependent on the type of phosphonic acid utilized in the preparation. Both aliphatic and aromatic organic phosphonates form these spherical aggregates. Functional groups, such as amino and carboxyl, may be introduced as part of the phosphonic acid or subsequently by further reaction, leading to a large family of naturally formed nanoparticles with accompanying microporosity.